Local Community Knowledge of Productivity and Diversity of Chicken Phenotypes (Gallus gallus domesticus) as an Effort to Support Ternate's Community Food Security - soenarsih sri; A. Hoda (Fakultas Peternakan, Universitas Padjadjaran, 2019)
Research with the title Local Community Knowledge of Productivity and Diversity of Chicken Phenotypes (Gallus gallus domesticus) as an Effort to Support Ternate's Community Food Security will be carried out with the aim of studying local knowledge about variations from local chickens, traditions in raising local chickens, and local chicken conservation efforts as studies beginning for the conservation of germplasm in supporting the food security of the people of Ternate City. This research will be carried out for 3 months. The location of the study was determined by purposive sampling with the provisions of the dominant research location having a local chicken population. The main material in this study were adult chickens, both male and female. Changing the phenotype of qualitative characteristics of chickens observed included: feather color, shank color (claw) and comb shape. To see the relationship between community knowledge about productivity and phenotype diversity, 67 interviewed native chicken farmers who are used to conducting selection in seed selection, based on their local knowledge system (LK). Operational Variables consist of independent variables and dependent variables. The independent variable is local knowledge of farmers with parameters: bones, feathers, combs, scales of feet, eyes, cloaca, anal bones, toes, head and back. While the dependent variable is the productivity of domestic chicken with parameters of average egg production per month during three months. The results showed that there was a significant correlation between local knowledge of the community and the level of egg production (P <0.01) with a correlation coefficient of 0.46. While for the phenotypic characterization of qualitative properties of free-range chicken in Ternate City, it is still quite diverse, both feather color, shank color and comb shape and do not yet have specific features that are firm, so that native chickens cannot be categorized as new varieties and selection to form superior and specific chicken varieties.